Sterilisasi Dan Penggunaan Zat Pengatur Tumbuh Bap (Benzile Amino Purin) Terhadap Pertumbuhan Eksplan Tunas Pisang Abaka (Musa Textilis Nee) Melalui Teknik In Vitro - Nathalia Unsong; Wenny Tilaar; Bertje R. A. Sumayku (Sam Ratulangi University, 2022)
This study aims to determine the most appropriate method and sterilization technique for the growth of abaca weevil shoot explants taken directly from the field and to determine the effect of the dose of growth regulator BAP (Benzile amino purine) on the growth of abaca feed. explants (Musa textilis Nee). through in vitro techniques. This study uses the multilevel sterilization method and the sterilization method using direct observation, namely when the explants have become shoots. The results showed that the appropriate sterilization method was a fixed sterilization method with bayclin treatment with a concentration of 30% for (30 minutes), 20% for (20 minutes), 10% for (10 minutes) with several techniques carried out so that the explant was successful. grow, namely in the 6th technique. Induction of shoots of abaka banana weevil explants in BAP treatment was best at 7 ppm treatment by producing 5 shoots. With the height of each shoot, namely: a (0.9 cm), b (0.3 cm), c (0.4 cm), d (0.4 cm), and e (0.5 cm).